Evolution, Moral Justification, and Moral Realism (Rivista Italiana di Filosofia Analitica Junior, 2012)
Does evolutionary theory have the potential to undermine morality? In his book The Evolution of Morality, Richard Joyce (2006) argues for a positive answer. He contends that an evolutionary account of morality would undermine moral judgements and lend support to moral scepticism. I offer a critique of Joyce’s argument. As it turns out, his case can be read in two different ways. It could beconstrued as an argument to establish a general scepticism about the justification of moral judgements. Or it could be read as an argument that targets only a particular meta-ethical position, namely moral realism. My claim is that it fails on both interpretations. There is no reason to believe that evolutionary considerations undermine morality.